1999
DOI: 10.1073/pnas.96.9.4953
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant protein A mediates mycoplasmacidal activity of alveolar macrophages by production of peroxynitrite

Abstract: We have previously shown that surfactant protein A (SP-A) mediates in vitro killing of mycoplasmas by alveolar macrophages (AMs) from resistant C57BL/6 mice through a nitric oxide (⅐NO)-dependent mechanism. Herein, SP-A-deficient [SP-A(؊/؊)] and inducible ⅐NO synthasedeficient [iNOS(؊/؊)] mice were infected intranasally with 10 5 or 10 7 colony-forming units of Mycoplasma pulmonis. SP-A(؊/؊) mice were as susceptible to mycoplasmal infection as highly susceptible C3H/He mice, and far more susceptible than resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
96
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(100 citation statements)
references
References 42 publications
(34 reference statements)
3
96
0
1
Order By: Relevance
“…Although it is possible compensatory adaptations to SP-A deficiency may obscure an important role in surfactant function, these mice have been useful in confirming a role for SP-A in pulmonary host defense against multiple microbes. SP-A-deficient mice clear pathogens from the lung slowly and have an exaggerated inflammatory response to microbial challenge (2,13,19,20), consistent with numerous in vitro studies (38). Mice deficient in SP-D display progressive postnatal inflammation without evidence for infection (3,18).…”
mentioning
confidence: 56%
“…Although it is possible compensatory adaptations to SP-A deficiency may obscure an important role in surfactant function, these mice have been useful in confirming a role for SP-A in pulmonary host defense against multiple microbes. SP-A-deficient mice clear pathogens from the lung slowly and have an exaggerated inflammatory response to microbial challenge (2,13,19,20), consistent with numerous in vitro studies (38). Mice deficient in SP-D display progressive postnatal inflammation without evidence for infection (3,18).…”
mentioning
confidence: 56%
“…Peroxynitrite is emerging as a major toxin among RNI and ROI, not only toward microbes but also toward mammalian cells (4,(30)(31)(32). Studies of the oxidative damage of proteins by peroxynitrite have focused on nitration of tyrosine residues and, to a lesser extent, oxidation of cysteines.…”
Section: Discussionmentioning
confidence: 99%
“…As a member of the collectin family of host defense proteins, SP-A also contributes to innate pulmonary immunity (11)(12)(13). We have previously studied M. pulmonis infection in B6 mice and showed that SP-A is necessary for maximal mycoplasma killing (4,14,15) by AM by upregulating the production of NO and reactive oxygen-nitrogen intermediates in these cells (14,15). Both SP-A Ϫ/Ϫ and iNOS Ϫ/Ϫ mice have a decreased ability to clear intratracheally instilled mycoplasmas.…”
Section: Clinical Relevancementioning
confidence: 99%
“…Mice were bred at the University of Alabama at Birmingham (UAB), and genotype was characterized from tail DNA as described previously (15). C57BL (C57BL/6J-Nos2 tm1Lau ) transgenic mice lacking the gene for iNOS (B6.iNOS Ϫ/Ϫ ) mice were obtained from the Jackson Laboratory (Bar Harbor, ME) (14) and were bred at UAB in autoclaved microisolator cages (Lab Products, Maywood, NJ). Mice of both sexes were used, and animals were maintained in a sterile environment and provided with autoclaved food (Agway, Syracuse, NY) and water ad libitum until being studied at 8-12 wk of age (20-25 g body weight).…”
Section: Animalsmentioning
confidence: 99%